Mediadores de Centros de Ciências e os seus papéis durante as visitas escolares - Silva, Camila Silveira da [UNESP]; Oliveira, Luiz Antonio Andrade de [UNESP] (My University, 2011)
In the present paper, it is presented a general view about who they are and the activities science centers and museums mediators develop. The literature points out to the diverse roles attributed to these actors and that the presence of this type of professional is a consolidated practice in non-formal educational institutions. Data obtained among the mediators of a science center during mediated school visits are also presented and discussed, focusing in the role attributed to these professionals, with the objective of characterizing their actions during these visits. The data obtained and analyzed showed that during school visits, the roles that are attributed to the mediators are: (a) mediation of the knowledge involved in the expositions; (b) explanation of the scientific concepts involved in the expositions; (c) presentation of the thematic spaces; (d) reception and organization of groups of visitors; (e) preservation of the physical and moral integrity of the visitors, and the integrity of the physical spaces and their equipments; (f) complementation of the school knowledge, and (g) diffusion of the scientific knowledge.

Neste artigo apresenta-se um panorama sobre quem são e o que fazem os mediadores de centros e museus de Ciência A literatura aponta os diversos papéis que possuem esses sujeitos e também que a presença desses profissionais nas instituições de educação não-formal já é algo consolidado. Também são apresentados e discutidos dados obtidos junto a mediadores de um centro de Ciências focando o papel desses sujeitos durante as visitas escolares mediadas, com o objetivo de caracterizar as ações que cabem a esses profissionais. Os dados construídos e analisados apontaram que, durante as visitas escolares, os papéis que cabem aos mediadores são: (a) mediar o conhecimento; (b) explicar os conceitos científicos envolvidos nas exposições; (c) apresentar os espaços temáticos; (d) receber e organizar os visitantes; (e) zelar pelo espaço físico e integridade física e moral dos visitantes; (f) complementar e ensino escolar dos visitantes e (g) difundir conhecimento científico.
Science centers mediators and their roles during school visits
Keywords: Mediadores; Centros e Museus de Ciências; Visitas Escolares Mediadas; Mediators; Centers and Museums of Sciences; Mediated School Visits